Studi Model Kepemimpinan terhadap Produktivitas Kerja Karyawan pada PT. Bank BTN KCP Syariah Jombang - Nanda Ochtafia; Mochammad Isa Anshori (Global Leadership Organizational Research in Management, 2024)
Employee productivity is one of the determining factors for the company's success in achieving its goals. Proper leadership implementation can increase employee productivity, especially in the banking sector. A leader in the banking sector must be able to unite perceptions (perspectives) in every element of the company, both employees and leaders of institutions in an effort to achieve the goals of financial institutions. This can be seen from the leadership style applied to one of the banking institutions in Indonesia, namely PT. State Savings Bank Jombang Sharia Sub-Branch Office. This research was conducted with the aim of knowing how to implement the leadership model at PT. BANK BTN KCP Syariah Jombang in relation to increasing employee productivity. This study uses the literature review method. Based on the results of literature studies, it can be seen that the leadership model at PT. BANK BTN KCP Syariah Jombang implemented is a democratic, charismatic, and transformational leadership model. Leadership plays an important role in employee productivity. This is because the application of a good leadership model will affect the morale, loyalty, work ethic, and company culture. If employees have a high.